Strategi Pemasaran Digital Lavojoy dalam Meningkatkan Loyalitas Konsumen - Erwin Permana; Lidya Putri Wulandari; Tambun Roma Tio Br Sihaloho; Riskon Ginting (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
The skin and hair care industry has experienced rapid growth in recent years. As the digital ecosystem becomes more established, various local products have the opportunity to emerge and exist in the market. Among the local products that have just emerged and found a place in the hearts of consumers is Lavojoy. Research on digital marketing strategies for imported products has been carried out very often, while for local products, especially skin and hair care products, has not been done much. This study aims to analyze Lavojoy's digital marketing strategy in increasing consumer loyalty. The research was conducted using a descriptive qualitative approach. Research data were obtained from the results of digital observations and data searches in various popular site databases related to the research problem. The results of the study show that the digital utilization strategy allows Lavojoy to build a loyal customer community through interactive content, collaboration with influencers, and active engagement through live and polling features. Two-way interactions carried out on Instagram, TikTok, and YouTube have a significant impact on brand awareness and customer emotional attachment to the brand. In addition, e-commerce optimization carried out through exclusive promo strategies, cashback, loyalty programs, and live shopping features has succeeded in increasing customer retention and encouraging repeat purchases. To increase the effectiveness of digital marketing strategies in the future, Lavojoy is advised to increase personalization in digital marketing by utilizing artificial intelligence (AI) and customer data analysis to offer a more personalized shopping experience, as well as developing content and product recommendations tailored to each customer's preferences, both through social media and e-commerce.